Public-on-private dual practice among physicians in public hospitals of Tigray National Regional State, North Ethiopia: perspectives of physicians, patients and managers - Goitom Gigar Abera; Yibeltal Kiflie Alemayehu; Jeph Herrin (BMC, 2017)
Abstract Background Physicians who work in the private sector while also holding a salaried job in a public hospital, known as "dual practice," is one of the main retention strategies adopted by the government of Ethiopia. Dual practice was legally endorsed in Tigray National Regional State, Ethiopia in 2010. Therefore, the aim of this study was to explore the extent of dual practice, reasons why physicians engage in it, and its effects on public hospital services in this state in northern Ethiopia. Methods A cross-sectional study using mixed methods was conducted from February to March 2011 in six geographically representative public hospitals of Tigray National Regional State. A semi-structured, self-administered questionnaire was distributed to all physicians working in the study hospitals, and an interviewer-administered, structured questionnaire was used to collect data from admitted patients. Focus group discussions were conducted with hospital governing boards. Quantitative and qualitative data were used in the analysis. Results Data were collected from 31 physicians and 449 patients in the six study hospitals. Six focus group discussions were conducted. Twenty-eight (90.3%) of the physicians were engaged in dual practice to some extent: 16 (51.6%) owned private clinics outside the public hospital, 5 (16.1%) worked part-time in outside private clinics, and 7 (22.6%) worked in the private wing of public hospitals. Income supplementation was the primary reason for engaging in dual practice, as reported by 100% of the physicians. The positive effects of dual practice from both managers' and physicians' perspectives were physician retention in the public sector. Ninety-one patients (20.3%) had been referred from a private clinic immediately prior to their current admission-a circular diversion pattern. Eighteen (19.8%) of the diverted patients reported that health workers in the public hospitals diverted them. Conclusions Circular diversion pattern of referral system is the key negative consequence of dual practice. Physicians and hospital managers agreed that health worker retention was the main positive consequence of dual practice upon the public sector, and banning dual practice would result in a major loss of senior physicians. The motive behind the circular diversion pattern described by patients should be studied further.